Changing in Dental Setting and Postural Analysis - Palandri , S. (New Horizons in Medicine and Medical Research Vol. 11, 2022)
Background: Dental structure and posture are closely linked to each other and now this is well known. Literature provides many articles to support this claim. The aim of this work is therefore not to provide yet another proof, but rather to highlight a peculiar characteristic of the case presented: a singular procedural asepsis, which makes it a particularly significant case. Nevertheless, this work aims to sensitize the operators who perform postural analyzes in relation to two aspects considered very important: 1 - the modification of the postural structure even in the absence of specific pathologies; 2 - the importance of maintaining procedural asepsis so that one does not fall into the risk of deductive automatisms, but always seeks unconditionally the origin of the disharmony that has emerged. Materials and Methods: The study began in 2020 and ended in 2021. The subject involved was a young woman of about 37 years old, weighing 52Kg and 1.58m tall, at the first postural analysis performed on 2020 January the third. Subsequently, two other postural analysis were performed, 13 months and 22 months after the first respectively. For the postural analysis, an identical protocol was followed in the three analysis performed. Results: Observing the results obtained in the three analysis, it can be deduced that approximately 63% of the controlled parameters (12 out of 19) underwent modifications, even if not all of them could be related to the variation of the dental setting. Conclusion: The study, even within the limits of its design, highlights how the different systems that make up the human body are interdependent and an action performed on one of them can be found as a modification of the initial state of others.